2015
DOI: 10.1002/jwmg.992
|View full text |Cite
|
Sign up to set email alerts
|

Northern bobwhite abundance in relation to precipitation and landscape structure

Abstract: Pereda-Solís, M. (2017). La abundancia de aves acuáticas (Anseriformes) en relación con la complejidad del paisaje en un sitio Ramsar del norte de México. Acta Zoológica Mexicana (n.s.), 33(2), 199-210. RESUMEN. La abundancia de aves acuáticas (Anseriformes) en re-lación con la complejidad del paisaje en un sitio Ramsar del norte de México. Se evaluó la respuesta de las poblaciones de aves acuáticas (Anseriformes) a la estructura del paisaje en un sitio Ramsar en el estado de Durango, México. Se delimitaron lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 48 publications
1
17
0
Order By: Relevance
“…We observed that spring cock call‐counts were modest predictors of minimum known populations and good predictors of mark–recapture estimates at the ranch scale, but were poor and insignificant predictors of density at the point scale. At the ranch scale, our results are similar to results of Parent et al (), who demonstrated a relatively strong correlation ( r = 0.68) between spring cock counts and helicopter indices (coveys/km) at the pasture scale (2,000 ha).…”
Section: Discussionsupporting
confidence: 91%
“…We observed that spring cock call‐counts were modest predictors of minimum known populations and good predictors of mark–recapture estimates at the ranch scale, but were poor and insignificant predictors of density at the point scale. At the ranch scale, our results are similar to results of Parent et al (), who demonstrated a relatively strong correlation ( r = 0.68) between spring cock counts and helicopter indices (coveys/km) at the pasture scale (2,000 ha).…”
Section: Discussionsupporting
confidence: 91%
“…Finally, it also is possible that the lack of precipitation prior to, and during, our study (2011–2014) negatively affected the bobwhite population and limited the population response to translocation. Precipitation has a profound influence on all aspects of bobwhite demographics (i.e., survival, reproduction, abundance) and often accounts for such a large portion of the variation in bobwhite population (Rice et al , Bridges et al , Parent et al ). For example, Hernández et al () documented that a lower percentage of females nested during a dry period (52.6%) versus a wet period (100%) in southern Texas.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we found no differences in vegetation composition or structure between years based on sampling and only differences in percent litter cover and visual obstruction among TSF. These observations are particularly important given that woody cover has been shown to be a critical component of nonbreeding bobwhite habitat (Wiseman and Lewis 1981, Roseberry and Klimstra 1984, Hiller et al 2007) and can buffer bobwhite populations from drought effects (Parent et al 2016).…”
Section: Discussionmentioning
confidence: 99%